2017
DOI: 10.1158/0008-5472.can-17-0202
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Is a Candidate Therapeutic Target for Myeloid Neoplasms with del(5q)

Abstract: Deletion of the chromosome 5q [del(5q)] is one of the most common cytogenetic abnormalities observed in patients with de novo myelodysplastic syndromes (MDS) and therapy-related MDS or acute myeloid leukemia (t-MDS/tAML). Emerging evidence indicates that activation of the Wnt/β-catenin pathway contributes to the development of myeloid neoplasms with del(5q). Whether β-catenin is a potential therapeutic target for myeloid neoplasms with del(5q) has yet to be evaluated. Here we report that genetic deletion of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Previous studies have reported that the Wnt/β-catenin pathway is related to cell development and proliferation [23][24][25]. Therefore, the present study considered the Wnt/β-catenin pathway as a target pathway for aspirin-induced apoptosis.…”
Section: Aspirin Inhibited the Canonical Wnt/β-catenin Pathway Of Tscmentioning
confidence: 99%
“…Previous studies have reported that the Wnt/β-catenin pathway is related to cell development and proliferation [23][24][25]. Therefore, the present study considered the Wnt/β-catenin pathway as a target pathway for aspirin-induced apoptosis.…”
Section: Aspirin Inhibited the Canonical Wnt/β-catenin Pathway Of Tscmentioning
confidence: 99%
“…Graded Wnt signaling has differential effects such that high activation leads to BM failure, while at a lesser degree, HSC expansion occurs . In one study, genetic deletion of a single allele of β‐catenin rescued ineffective hematopoiesis in an Apc haploinsufficient mouse model with several characteristics of del(5q) MDS . Suppression of β‐catenin by indomethacin or shRNA also led to reduced proliferation and survival of human leukemia cells with del(5q) but not of control leukemia cell lines in vitro .…”
Section: Wnt/β‐catenin Signaling In Hsc Expansionmentioning
confidence: 72%
“…45 β-catenin inactivation also inhibited the progression to leukemia in xenograft mice reconstituted with del(5q) leukemia cell lines. 45 These data suggest that the Wnt/β-catenin pathway may be a key therapeutic target for del(5q) MDS.…”
Section: W Nt/β -C Atenin S I G Naling In H Sc E Xpans Ionmentioning
confidence: 95%
See 2 more Smart Citations